The trying game : get through fertility treatment and get pregnant without losing your mind - Klein, Amy (Ballantine Books, 2020)
After her own infertility struggles, Amy Klein wrote the book she wished she had in the midst of IVF, miscarriages, and countless doctor's appointments. She includes advice from medical experts and their patients along with questions to ask along the way.